A sinter production method with differential pretreatment and synergistic addition of magnesium flux

CN122979615APending Publication Date: 2026-10-27德龙钢铁有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611333998.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]烧结矿是高炉炼铁的主要含铁炉料,其MgO含量通常需控制在1.5%~2.5%范围内,以改善高炉渣流动性和烧结矿的高温冶金性能;目前工业生产中普遍采用单一白云石或菱镁矿作为镁源,经简单破碎、筛分后直接参与一次混合制粒;然而,白云石与菱镁矿的分解起始温度和分解速率差异显著:菱镁矿分解温度较高且分解集中,白云石则分两步分解且起始温度较低,二者热分解行为难以在烧结料层自上而下的温度梯度中同步匹配;这种单一熔剂粗放式配加方式容易造成MgO在烧结矿中局部富集或贫化,导致铁酸钙液相生成量波动,烧结矿矿物组成不稳定,转鼓强度与还原性指标难以兼顾;现有技术多聚焦于熔剂种类替换或MgO总量控制,缺乏针对不同镁熔剂热分解特性差异的系统性处理策略,未能将熔剂预处理、粒度分级、添加时序与烧结热制度进行耦合设计;因此,亟需开发一种以镁熔剂差异化处理为核心、通过多种镁熔剂协同配加和分步调控,实现熔剂热行为匹配与MgO均匀分布的烧结矿生产方法

Benefits of technology

1.通过按分解温度和分解速度对熔剂进行分级,针对性地进行预处理,使不同熔剂在烧结过程的适宜温度区间释放MgO,充分发挥各类熔剂特性,由于快分解高活性熔剂更加容易分解,而通过将快分解高活性熔剂布料于料层上部,利用上部温度相对较低的特点,控制了其分解速度不至于过快,同时还能再相对低的温度下进行一定的分解,同时由于慢分解稳定性熔剂相对不容易分解,从而本发明将慢分解稳定性熔剂布料于料层下部,利用下部相对较高的温度而实现其分解不至于过慢,从而使得使熔剂分解与料层温度相匹配,从而改善了熔剂的分解效率,熔剂利用率提高15~25%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979615A_ABST
    Figure CN122979615A_ABST
Patent Text Reader

Abstract

The application discloses a sinter production method of magnesium flux differential pretreatment and synergistic addition, and belongs to the technical field of steel metallurgy sintering equipment, and comprises the following steps: step one, grading magnesium flux; step two, fine grinding part of fast-decomposing high-activity flux and performing surface coating inhibitor treatment; performing light burning treatment on slow-decomposing stable flux; step three, uniformly mixing the slow-decomposing stable flux in step two with fuel to obtain fuel flux composite material; step four, mixing the fuel flux composite material, iron ore powder and active lime for the first time; then mixing the first mixture with the fast-decomposing high-activity flux mixture to obtain a second mixture; step five, arranging three independent hoppers above the sintering trolley in the running direction of the trolley, and the feeding ports of the hoppers correspond to the lower layer, the middle layer and the upper layer of the material on the trolley respectively; and step six, performing induced draft sintering by distributing the mixture to the sintering trolley for sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux, specifically a method that separates magnesium-containing solvents into fast-decomposing high-activity fluxes and slow-decomposing stable fluxes, performs particle size control and pretreatment on each, and then synergistically adds them stepwise to the sintering mixture to achieve uniform distribution of MgO in the sintered ore. This method belongs to the technical field of sintering equipment in iron and steel metallurgy. Background Technology

[0002] Sinter is the main iron-containing charge in blast furnace ironmaking. Its MgO content usually needs to be controlled within the range of 1.5% to 2.5% to improve the fluidity of blast furnace slag and the high-temperature metallurgical properties of sinter. Currently, in industrial production, dolomite or magnesite is commonly used as the magnesium source. After simple crushing and screening, it is directly involved in primary mixing and granulation. However, dolomite and magnesite have significant differences in decomposition initiation temperature and decomposition rate: magnesite has a higher decomposition temperature and concentrated decomposition, while dolomite decomposes in two steps and has a lower initiation temperature. The thermal decomposition behavior of the two is difficult to match synchronously in the temperature gradient from top to bottom of the sintering bed. This crude method of using a single flux is problematic. Adding MgO can easily lead to local enrichment or depletion of MgO in sinter, resulting in fluctuations in the amount of calcium ferrite liquid phase generated, unstable mineral composition of sinter, and difficulty in simultaneously achieving drum strength and reducibility. Existing technologies mostly focus on flux type replacement or total MgO control, lacking a systematic treatment strategy for the differences in thermal decomposition characteristics of different magnesium fluxes, and failing to couple flux pretreatment, particle size classification, addition sequence, and sintering thermal regime design. Therefore, there is an urgent need to develop a sinter production method that takes differentiated magnesium flux treatment as the core, and achieves flux thermal behavior matching and uniform MgO distribution through the synergistic addition and step-by-step control of multiple magnesium fluxes. Summary of the Invention

[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a sinter production method with differentiated pretreatment and synergistic addition of magnesium flux, which can achieve the goal of uniform distribution of MgO in sinter.

[0004] The problem described in this invention is solved by the following technical solution: A method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux includes the following steps: Step 1: Classify magnesium-containing fluxes into fast-decomposing, highly active fluxes and slow-decomposing, stable fluxes based on their decomposition temperature and rate. Step 2: Finely grind 75wt% to 85wt% of the total mass of the fast-decomposing high-activity flux, controlling the particle size to ≤0.5mm. Do not finely grind the remainder. Coat the surface of the finely ground fast-decomposing high-activity flux with inhibitors, controlling the particle size after coating to 2mm to 3mm, to obtain the fast-decomposing high-activity flux mixture. 75wt% to 85wt% of the total mass of the slow-decomposition stable flux was lightly calcined, and the remainder was not lightly calcined; the light calcination temperature was 800℃ to 1000℃, and the particle size was controlled to be 1 mm to 3 mm after light calcination. Step 3: Mix the slow-decomposition stable flux that has undergone light burning treatment in Step 2 with the fuel to obtain a fuel flux composite material; Step 4: Mix the fuel flux composite, iron ore powder, and quicklime at a mass percentage of 7%–18%, 80%–90%, and 2%–3% of the total mass, respectively, with the sum of the three being 100%, to obtain a first mixture; then place the first mixture into a secondary mixer, and simultaneously add the fast-decomposition high-activity flux mixture obtained in Step 2, and mix them together with the first mixture to obtain a second mixture; Step 5: Set up three independent hoppers above the sintering machine trolley along the trolley's running direction. The feed ports of each hopper correspond to the lower, middle, and upper layers of material on the trolley, respectively. By controlling the opening of each feed port and the feeding sequence, a layered material layer of bottom, middle, and top layers is formed on the trolley. Specifically, the remaining amount of the slow-decomposition stable flux from Step 2 is distributed above the trolley grate bars to form the lower area of ​​the material layer. Then, the second mixture is distributed to form the middle area of ​​the material layer. Finally, the remaining amount of the fast-decomposition highly active flux from Step 2 is distributed to the upper area of ​​the material layer. Step 6: Exhaust ventilation sintering. The mixture is fed onto the sintering trolley for sintering.

[0005] In the above-mentioned method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux, in step one, the fast-decomposition highly active flux is a magnesium-containing flux that rapidly decomposes and releases MgO in the low-temperature sintering zone, and the slow-decomposition stable flux is a magnesium-containing flux that slowly decomposes and releases MgO in the high-temperature sintering zone; wherein, the temperature range of the low-temperature sintering zone is within 700℃~1100℃, and the temperature range of the high-temperature sintering zone is within 1100℃~1400℃.

[0006] In the above-mentioned method for producing sintered ore by differential pretreatment and synergistic addition of magnesium flux, in step three, the slow-decomposition stable flux that has undergone light burning treatment is premixed with fuel at a mass ratio of 1:(1-3), and the mixing time is controlled at 1-2 min.

[0007] In the above-mentioned method for producing sintered ore by differential pretreatment and synergistic addition of magnesium flux, in step four, during the first mixing process, the active lime and fuel flux composite are mixed in advance, and then mixed with iron ore powder. The first mixing time is 3 min to 5 min, and the second mixing time is 3 min to 4 min. Water is added during the mixing process to control the moisture content of the mixture at 7.0% to 8.0%.

[0008] In the above-mentioned method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux, in step five, the sintered material layer is divided from bottom to top along the thickness direction, with the bottom of the trolley as the reference: bottom layer, middle layer, and surface layer; the bottom layer area is the range ≥0 and ≤200mm from the bottom of the trolley; the middle layer area is the range >200 and ≤600mm from the bottom of the trolley; and the surface layer area is the range from >600mm from the bottom of the trolley to the top surface of the material layer.

[0009] In the above-mentioned method for producing sintered ore by differential pretreatment and synergistic addition of magnesium flux, in step one, the fast-decomposition high-activity flux is one or more of light-calcined magnesia powder, light-calcined dolomite powder, or magnesite powder, and the slow-decomposition stable flux is one or more of dolomite, serpentine, or olivine; the mass ratio of the fast-decomposition high-activity flux to the slow-decomposition stable flux is 1:(1-2).

[0010] In the above-mentioned method for producing sintered ore by differentiated pretreatment and synergistic addition of magnesium flux, in step two, the inhibitor is one or more of water glass, lignin sulfonate or starch, and the amount of inhibitor added accounts for 0.5% to 2.0% of the mass of the rapidly decomposing high-activity flux after fine grinding.

[0011] In the above-mentioned method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux, in step four, the CaO mass fraction of the active lime is ≥85%; and the activity is ≥300mL after 10min as determined by titration with 4mol / L hydrochloric acid.

[0012] In the above-mentioned method for producing sinter by differential pretreatment and synergistic addition of magnesium flux, in step six, the MgO content in the final sinter product is 2.0% to 3.0%.

[0013] The beneficial effects of this invention are as follows: 1. By classifying fluxes according to their decomposition temperature and rate, and performing targeted pretreatment, different fluxes release MgO within the appropriate temperature range during sintering, fully utilizing the characteristics of each flux. Since fast-decomposing, highly active fluxes are easier to decompose, by placing them in the upper part of the material layer, the relatively lower temperature at the top is utilized to control their decomposition rate and prevent them from being too fast. At the same time, they can still undergo some decomposition at a relatively low temperature. Meanwhile, since slow-decomposing, stable fluxes are relatively difficult to decompose, this invention places them in the lower part of the material layer, utilizing the relatively higher temperature at the bottom to prevent their decomposition from being too slow. This ensures that the flux decomposition matches the material layer temperature, thereby improving the flux decomposition efficiency and increasing flux utilization by 15-25%.

[0014] 2. Fine grinding and encapsulation of inhibitors are applied to rapidly decomposing, highly active fluxes to effectively suppress the premature release of MgO in the low-temperature zone, allowing MgO to be released mainly in the high-temperature zone during sintering, thus promoting mineralization reactions and improving the mineral composition and structure of sintered ores.

[0015] 3. By layering the flux, the slow-decomposition stable flux is concentrated in the high-temperature zone at the bottom of the material layer, while the fast-decomposition highly active flux is concentrated in the upper part of the material layer. This achieves an optimized configuration of the flux in the vertical direction, which is more conducive to the transformation of magnesium-bearing magnetite into the complex calcium ferrite phase. Due to the heat storage effect of the material layer, the vertical temperature distribution is "cold at the top and hot at the bottom". By placing the slow-decomposition stable flux with a high decomposition temperature and slow decomposition rate in the lower high-temperature zone, it can be fully decomposed under sufficient heat conditions. At the same time, the fast-decomposition highly active flux with a low decomposition temperature and high reactivity is placed in the upper low-temperature zone. Its rapid decomposition characteristics can be used to quickly provide CaO at a lower temperature, ensuring the uniformity and sufficiency of flux decomposition throughout the material layer and providing sufficient reactants for the complex calcium ferrite. Furthermore, since magnesium-bearing magnetite has a higher transformation temperature to the complex calcium ferrite phase compared to magnetite, placing the slow-decomposition stable flux in the lower high-temperature zone is conducive to the formation of complex calcium ferrite, thereby improving the mineral composition and microstructure of the sinter.

[0016] 4. The adoption of a two-stage mixing process and fuel-flux premixing technology improves the contact conditions between the flux and iron ore powder, promotes ore formation, and increases the strength and reducibility of the sinter drum by 1-2%. The first mixing stage uses a cylindrical mixer for dry mixing and water wetting, ensuring that the iron ore powder, flux, fuel, and other components are initially mixed and reach a suitable moisture content. The second mixing stage involves enhanced granulation; by controlling the mixing time and speed, fine particles adhere to the surface of coarse particles to form granulated balls, improving the permeability of the mixture. The key technology lies in premixing the solid fuel with active lime, forming a "fuel-flux core" structure. This allows the surface of the fuel particles to be uniformly coated with a flux powder layer. During sintering, the flux powder coating the surface melts synchronously to form a liquid phase, ensuring a high degree of overlap between the high-temperature zone and the liquid phase generation zone. The liquid phase can fully wet and dissolve the surrounding iron ore powder particles. Together, they promoted the formation of high-strength binder phases such as calcium ferrite, optimized the mineral composition and pore structure of the sinter, and thus improved the drum strength and reducibility of the sinter. Attached Figure Description

[0017] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0018] See Figure 1 The present invention comprises the following steps: Step 1: Classify magnesium-containing fluxes into fast-decomposing, highly active fluxes and slow-decomposing, stable fluxes based on their decomposition temperature and rate. The fast-decomposition highly active flux is a magnesium-containing flux that rapidly decomposes and releases MgO in the low-temperature sintering zone, and the slow-decomposition stable flux is a magnesium-containing flux that slowly decomposes and releases MgO in the high-temperature sintering zone; wherein the temperature range of the low-temperature sintering zone is 700℃~1100℃, and the temperature range of the high-temperature sintering zone is 1100℃~1400℃.

[0019] Step 2: Finely grind 75wt% to 85wt% of the total mass of the fast-decomposing high-activity flux, controlling the particle size to ≤0.5mm. Do not finely grind the remainder. Coat the surface of the finely ground fast-decomposing high-activity flux with inhibitors to inhibit the premature release of MgO in the low-temperature zone. Control the particle size after coating to 2 mm to 3 mm to obtain the fast-decomposing high-activity flux mixture. 75wt% to 85wt% of the total mass of the slow-decomposition stable flux was lightly calcined, while the remainder was not lightly calcined. The light calcination temperature was 800℃ to 1000℃, and the particle size was controlled to be 1 mm to 3 mm after light calcination. The purpose of this was to improve its reactivity in the medium and high temperature range. Step 3: Mix the slow-decomposition stable flux that has undergone light burning treatment in Step 2 with the fuel to obtain a fuel flux composite material; Step 4: Mix the fuel flux composite, iron ore powder, and quicklime at a mass percentage of 7%–18%, 80%–90%, and 2%–3% of the total mass, respectively, with the sum of the three being 100%, to obtain a first mixture; then place the first mixture into a secondary mixer, and simultaneously add the fast-decomposition high-activity flux mixture obtained in Step 2, and mix them together with the first mixture to obtain a second mixture; Step 5: Set up three independent hoppers above the sintering machine trolley along the trolley's running direction. The feed ports of each hopper correspond to the lower, middle, and upper layers of material on the trolley, respectively. By controlling the opening of each feed port and the feeding sequence, a layered material layer of bottom, middle, and top layers is formed on the trolley. Specifically, the remaining amount of the slow-decomposition stable flux from Step 2 is distributed above the trolley grate bars to form the lower area of ​​the material layer. Then, the second mixture is distributed to form the middle area of ​​the material layer. Finally, the remaining amount of the fast-decomposition highly active flux from Step 2 is distributed to the upper area of ​​the material layer. A fast-decomposing, highly active flux rapidly supplies magnesium to the surface layer, while a slow-decomposing, stable flux continuously supplies magnesium to the bottom layer. The combination of the two can significantly reduce the deviation of MgO content in the upper, middle, and lower layers, avoiding local MgO enrichment or deficiency caused by a single flux.

[0020] Step 6: Exhaust ventilation sintering. The mixture is fed onto the sintering trolley for sintering. The material layer thickness is controlled at 750mm to 950mm, the ignition temperature is 1150 to 1250℃, the ignition time is 1 to 2 minutes, and exhaust ventilation sintering is performed. The final sintering temperature is controlled at 1250 to 1350℃.

[0021] In step three, the slow-decomposition stable flux that has undergone light burning treatment is premixed with the fuel at a mass ratio of 1:(1-3), and the mixing time is controlled at 1-2 min.

[0022] In step four, during the first mixing process, the active lime and fuel flux composite are mixed in advance, and then mixed with iron ore powder. The first mixing time is 3 min to 5 min, and the second mixing time is 3 min to 4 min. Water is added during the mixing process to control the moisture content of the mixture at 7.0% to 8.0%.

[0023] In step five, taking the bottom of the trolley as a reference, the sintered material layer is divided into three layers from bottom to top along the thickness direction: bottom layer, middle layer, and surface layer. The bottom layer area is the range ≥0 and ≤200mm from the bottom of the trolley; the middle layer area is the range >200 and ≤600mm from the bottom of the trolley; and the surface layer area is the range from >600mm from the bottom of the trolley to the top surface of the material layer.

[0024] In step one, the fast-decomposition highly active flux is one or more of light-burned magnesia powder, light-burned dolomite powder, or magnesite powder, and the slow-decomposition stable flux is one or more of dolomite, serpentine, or olivine; the mass ratio of the fast-decomposition highly active flux to the slow-decomposition stable flux is 1:(1-2).

[0025] In step two, the inhibitor is one or more of water glass, lignin sulfonate or starch, and the amount of inhibitor added accounts for 0.5% to 2.0% of the mass of the rapidly decomposing high-activity flux after fine grinding.

[0026] In step four, the CaO mass fraction of the active lime is ≥85%; the activity is ≥300mL after 10 minutes by titration with 4mol / L hydrochloric acid.

[0027] In step six, the MgO content in the final sintered ore product is 2.0% to 3.0%. Example 1

[0028] I. Classification of magnesium-containing fluxes: Magnesium-containing fluxes are classified into fast-decomposing high-activity fluxes and slow-decomposing stable fluxes according to their decomposition temperature and decomposition rate; the fast-decomposing high-activity flux is light-burned magnesium oxide powder, and the slow-decomposing stable flux is dolomite; the ratio of light-burned magnesium oxide powder to dolomite is 1:1.5. II. Pretreatment of Magnesium-Containing Flux: 75wt%–85wt% of the graded fast-decomposition high-activity flux was finely ground to control the particle size ≤0.5mm. Inhibitors were coated onto the surface of the finely ground particles, controlling the particle size after coating to 2–3mm; this inhibited premature MgO release in the low-temperature region. 75wt%–85wt% of the slow-decomposition stable flux was lightly calcined at 900℃, controlling the particle size after calcination to 1–3mm, thereby improving its reactivity in the medium- and high-temperature regions. The inhibitor was starch, and the amount of inhibitor used was 1.0% of the mass of the finely ground fast-decomposition high-activity flux. 3. The slow-decomposition stable flux after light burning treatment and particle size control is mixed with the fuel in advance; the slow-decomposition stable flux after light burning treatment is premixed with the fuel at a mass ratio of 1-2, and the premixing time is 1.5 min. IV. Graded Mixing: The fuel flux composite material, iron ore powder, and quicklime are mixed at a mass ratio of 10:87:3 for 3 minutes to obtain a primary mixture. The primary mixture is then placed into a secondary mixer, and a fast-decomposing high-activity flux mixture is added at the same time. The mixture is then mixed with the primary mixture for 4 minutes, and the moisture content of the mixture is controlled at 7.8% to obtain a secondary mixture. V. Layered distribution of remaining magnesium-containing flux: Layered distribution is achieved by controlling the opening and feeding sequence of each feed port; the remaining slow-decomposition stable flux after classification is first distributed above the grate bars of the trolley through the lower feed port to form the lower region of the material layer; then the mixed material is normally distributed through the middle feed port to form the middle region of the material layer; finally, the remaining fast-decomposition highly active flux after classification is distributed in the upper region of the material layer through the upper feed port. VI. Exhaust Sintering: The mixture is fed onto the sintering trolley for sintering. The material layer thickness is controlled at 800 mm, the ignition temperature is 1200℃, the ignition time is 1.5 min, and the final sintering temperature is controlled at 1300℃. Finally, the sinter produced by exhaust sintering has an MgO content of 2.5% and a binary basicity of 1.9.

[0029] Using this method, in Example 1, the consumption of solid fuel during sintering was detected, and the drum strength and reducibility of the finished sinter were tested. The results are shown in Table 6.

[0030] Table 6. Key Sintering Indicators of Example 1 Comparative Example 1 Comparative Example 1 uses the same proportions of fluxes, raw materials and fuels as Example 1, but does not classify the magnesium-containing fluxes. Instead, it directly uses the existing production process for primary and secondary mixing operations, and does not control the flux distribution at different material layer heights. The consumption of sintering solids under this method was tested, and the drum strength and reducibility of the finished sinter were tested. The results are shown in Table 1.

[0031] Table 1. Key sintering indicators of Comparative Example 1 52.4 76.1 2.28 78.5 Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the flux distribution in the layered fabric is reversed; that is, the lower region of the material layer is enriched with fast-decomposing, highly active flux, while the upper region is enriched with slow-decomposing, stable flux. The remaining steps are consistent with Example 1. The consumption of sintered solids under this method was measured, and the drum strength and reducibility of the finished sinter were tested. The results are shown in Table 2.

[0032] Table 2. Key sintering indicators of Comparative Example 2 52.1 75.6 2.29 78.0 Comparative Example 3 The difference between this comparative example and Example 1 is that all fast-decomposing high-activity fluxes and slow-decomposing stable fluxes are not layered and distributed, but are directly mixed using a single-mixing and two-mixing process. After being mixed evenly, they are directly segregated and distributed. The flux treatment methods involved in the remaining steps are consistent, but the distribution position is no longer differentiated. The consumption of sintering solids under this method is detected, and the drum strength and reducibility of the finished sinter are tested. The results are shown in Table 3.

[0033] Table 3. Key sintering indicators of Comparative Example 3 51.7 76.4 2.24 78.4 Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the graded fast-decomposition high-activity flux and slow-decomposition stable flux are not pretreated, that is, steps two, three and four are skipped; the two untreated fluxes are directly layered and distributed according to the requirements of step five; the consumption of sintering solids under this method is detected and the drum strength and reducibility of the finished sinter are tested, and the results are shown in Table 4.

[0034] Table 4. Key sintering indicators of Comparative Example 4 50.4 76.1 2.28 79.5 Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the fast-decomposing high-activity flux and the slow-decomposing stable flux are not pre-graded and mixed. Instead, according to the total amount and proportion of the two types of flux added in step four of Example 1, the two types of flux are weighed separately, and a portion of the fast-decomposing high-activity flux and a portion of the slow-decomposing stable flux are added simultaneously during the first mixing process. During the second mixing process, the remaining fast-decomposing high-activity flux and the remaining slow-decomposing stable flux are added simultaneously. The remaining steps are the same as in Example 1, and the results are shown in Table 5. The slow-decomposing stable flux mentioned in Comparative Example 5 refers to the slow-decomposing stable flux in the fuel flux composite material that has undergone light burning treatment.

[0035] Table 5. Key sintering indicators of Comparative Example 5 49.3 76.7 2.26 80.5 Comparing Tables 1 and 6, it can be seen that the solid consumption of sintering fuel in Comparative Example 1 is 52.4 kg·t. -1 The solid fuel consumption in Example 1 was 48.7 kg·t. -1 The drum strength of the finished sinter of Comparative Example 1 was 76.1%, while that of Example 1 was 77.4%. The reducibility of Comparative Example 1 was 78.5%, while that of Example 1 was 81.9%. This means that after using the method of producing sinter with different magnesium fluxes of the present invention, the consumption of sinter solids was reduced, and the drum strength and reducibility of the sinter were improved. It can be concluded that the method utilizes the heat storage effect of thick-layer sintering, improves the flux utilization rate, is conducive to the formation of composite calcium ferrite, reduces sintering fuel consumption, improves the quality of sinter, and plays a role in cost reduction and quality improvement.

[0036] Comparing Tables 2 and 6, it can be seen that, based on the comparison of the key sintering index data of Example 1 and Comparative Example 2, the consumption of sintering solids is reduced and the drum strength and reducibility of the sinter are improved after the flux is correctly layered and distributed. This is because the correct layering and distribution of flux utilizes the longitudinal temperature distribution of the sintering material layer, matching the flux decomposition temperature with the material layer temperature, which is conducive to the formation of composite calcium ferrite in the sinter, reduces the consumption of sintering solid fuel, and improves the quality of the sinter.

[0037] Comparing Tables 3 and 6, it can be seen that, based on the comparison of the key sintering index data of Example 1 and Comparative Example 3, the consumption of sintering solids is reduced after the flux is layered and distributed, and the drum strength and reducibility of the sinter are improved.

[0038] Comparing Tables 4 and 6, it can be seen that, based on the comparison of the key sintering index data of Example 1 and Comparative Example 4, the consumption of sintering solids is reduced after flux pretreatment, and the drum strength and reducibility of sinter are improved.

[0039] Comparing Tables 5 and 6, it can be seen that, based on the comparison of the key sintering index data of Example 1 and Comparative Example 5, the consumption of sintering solids is reduced after the flux is graded and mixed, and the drum strength and reducibility of the sinter are improved.

Claims

1. A method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux, characterized in that, Includes the following steps: Step 1: Classify magnesium-containing fluxes into fast-decomposing, highly active fluxes and slow-decomposing, stable fluxes based on their decomposition temperature and rate. Step 2: Finely grind 75wt% to 85wt% of the total mass of the fast-decomposing high-activity flux, controlling the particle size to ≤0.5mm. Do not finely grind the remainder. Coat the surface of the finely ground fast-decomposing high-activity flux with inhibitors, controlling the particle size after coating to 2mm to 3mm, to obtain the fast-decomposing high-activity flux mixture. 75wt% to 85wt% of the total mass of the slow-decomposition stable flux was lightly calcined, and the remainder was not lightly calcined; the light calcination temperature was 800℃ to 1000℃, and the particle size was controlled to be 1 mm to 3 mm after light calcination. Step 3: Mix the slow-decomposition stable flux that has undergone light burning treatment in Step 2 with the fuel to obtain a fuel flux composite material; Step 4: Mix the fuel flux composite, iron ore powder, and quicklime at a mass percentage of 7%–18%, 80%–90%, and 2%–3% of the total mass, respectively, with the sum of the three being 100%, to obtain a first mixture; then place the first mixture into a secondary mixer, and simultaneously add the fast-decomposition high-activity flux mixture obtained in Step 2, and mix them together with the first mixture to obtain a second mixture; Step 5: Set up three independent hoppers above the sintering machine trolley along the trolley's running direction. The feed ports of each hopper correspond to the lower, middle, and upper layers of material on the trolley, respectively. By controlling the opening of each feed port and the feeding sequence, a layered material layer of bottom, middle, and top layers is formed on the trolley. Specifically, the remaining amount of the slow-decomposition stable flux from Step 2 is distributed above the trolley grate bars to form the lower area of ​​the material layer. Then, the second mixture is distributed to form the middle area of ​​the material layer. Finally, the remaining amount of the fast-decomposition highly active flux from Step 2 is distributed to the upper area of ​​the material layer. Step 6: Exhaust ventilation sintering. The mixture is fed onto the sintering trolley for sintering.

2. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step one, the fast-decomposition highly active flux is a magnesium-containing flux that rapidly decomposes and releases MgO in the low-temperature sintering zone, and the slow-decomposition stable flux is a magnesium-containing flux that slowly decomposes and releases MgO in the high-temperature sintering zone; wherein, the temperature range of the low-temperature sintering zone is within 700℃~1100℃, and the temperature range of the high-temperature sintering zone is within 1100℃~1400℃.

3. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step three, the slow-decomposition stable flux that has undergone light burning treatment is premixed with the fuel at a mass ratio of 1:(1-3), and the mixing time is controlled at 1-2 min.

4. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step four, during the first mixing process, the active lime and fuel flux composite are mixed in advance, and then mixed with iron ore powder. The first mixing time is 3 min to 5 min, and the second mixing time is 3 min to 4 min. Water is added during the mixing process to control the moisture content of the mixture at 7.0% to 8.0%.

5. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step five, taking the bottom of the trolley as a reference, the sintered material layer is divided into three layers from bottom to top along the thickness direction: bottom layer, middle layer and surface layer; the bottom layer area is the range ≥0 and ≤200mm from the bottom of the trolley; the middle layer area is the range >200 and ≤600mm from the bottom of the trolley; the surface layer area is the range from >600mm from the bottom of the trolley to the top surface of the material layer.

6. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step one, the fast-decomposition highly active flux is one or more of light-burned magnesia powder, light-burned dolomite powder, or magnesite powder, and the slow-decomposition stable flux is one or more of dolomite, serpentine, or olivine; the mass ratio of the fast-decomposition highly active flux to the slow-decomposition stable flux is 1:(1-2).

7. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step two, the inhibitor is one or more of water glass, lignin sulfonate or starch, and the amount of inhibitor added accounts for 0.5% to 2.0% of the mass of the rapidly decomposing high-activity flux after fine grinding.

8. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step four, the CaO mass fraction of the active lime is ≥85%; the activity is ≥300mL after 10 minutes by titration with 4mol / L hydrochloric acid.

9. The method for producing sintered ore using differentiated pretreatment and synergistic addition of magnesium flux according to claim 1, characterized in that: In step six, the MgO content in the final sintered ore product is 2.0% to 3.0%.